The Effect of Technical Discussion Group Guidance on Students’ Academic Procrastination Amid The Covid-19 Pandemic - Ariyadi Suryo Sumoadi; Suci Prasasti; Usmani Haryanti (Pamomong: Journal of Islamic Educational Counseling, 2022)
The purpose of this study was to determine the effect of group guidance services with discussion technique on academic procrastination of students of Vocational High School 4 in Surakarta amid the covid-19 pandemic. The research method used is an experimental method with a research design of one group design pre-test and post-test. This method was carried out by giving a pre-test before being treated with group guidance services with discussion techniques and then a post-test after being given treatment. The results of the pre-test and post-test data will show whether there is a difference between before and after being given the treatment. The sampling technique used was purposive sampling, by taking 12 students of class X majoring in Catering. The data was collected using questionnaires, interviews, and documentation. The data was then analysed using paired sample t-test which shows the value of tcount ttable, which is 12,784 2,200. The results also showed a significance value of 0.000 0.05. The value of the comparison of pre-test and post-test from the results of the paired sample t-test shows the number of 17.33. To sum up, the study showed the difference between the results of the pre-test and post-test which implies the significance influence of discussion technique group guidance services on the academic procrastination of students class X majoring in Catering at Surakarta Vocational High School 4 during the pandemic.